High-quality chromosome-scale assembly of the walnut (Juglans regia L.) reference genome. Issue 5 (20th May 2020) - Marrano, Annarita; Britton, Monica; Zaini, Paulo A; Zimin, Aleksey V; Workman, Rachael E; Puiu, Daniela; Bianco, Luca; Pierro, Erica Adele Di; Allen, Brian J; Chakraborty, Sandeep; Troggio, Michela; Leslie, Charles A; et al.
Abstract: Background: The release of the first reference genome of walnut ( Juglans regia L.) enabled many achievements in the characterization of walnut genetic and functional variation. However, it is highly fragmented, preventing the integration of genetic, transcriptomic, and proteomic information to fully elucidate walnut biological processes. Findings: Here, we report the new chromosome-scale assembly of the walnut reference genome (Chandler v2.0) obtained by combining Oxford Nanopore long-read sequencing with chromosome conformation capture (Hi-C) technology. Relative to the previous reference genome, the new assembly features an 84.4-fold increase in N50 size, with the 16 chromosomal pseudomolecules assembled and representing 95% of its total length. Using full-length transcripts from single-molecule real-time sequencing, we predicted 37, 554 gene models, with a mean gene length higher than the previous gene annotations. Most of the new protein-coding genes (90%) present both start and stop codons, which represents a significant improvement compared with Chandler v1.0 (only 48%). We then tested the potential impact of the new chromosome-level genome on different areas of walnut research. By studying the proteome changes occurring during male flower development, we observed that the virtual proteome obtained from Chandler v2.0 presents fewer artifacts than the previous reference genome, enabling the identification of a new potential pollen allergen in walnut. Also, the new chromosome-scale genome facilitates in-depth studies of intraspecies genetic diversity by revealing previously undetected autozygous regions in Chandler, likely resulting from inbreeding, and 195 genomic regions highly differentiated between Western and Eastern walnut cultivars. Conclusion: Overall, Chandler v2.0 will serve as a valuable resource to better understand and explore walnut biology.